Engklek: Ethnomathematics-Based Traditional Games in The Development of Teaching Materials to Build Mathematical Literacy Skills - Adi Asmara; Vera Septi Andrini; Yayang Alfian Juwanto; Andi Muhammad Irfan Taufan Asfar; Rahmat Jumri; Ahmad Yani T (PT. Anagata Sembagi Education, 2024)
Changes in Indonesia’s educational curriculum emphasize the importance of students' reasoning skills in mathematics. However, Indonesia's low ranking in the PISA assessment, particularly in mathematics, highlights students limited mathematical literacy. One major contributing factor is the fear and anxiety students feel towards mathematics, which is often viewed as intimidating. This study aims to review literature on the impact of integrating geometry-based mathematics learning with the traditional game engklek. The research method employed is a Systematic Literature Review (SLR) using the SALSA framework and a descriptive analysis approach. Data were gathered from 17 articles published between 2014 and 2024, covering reputable international journals, accredited national journals, and journals indexed by DOAJ and Copernicus. The analysis identified 9 articles reporting that geometry topics requiring reasoning and literacy skills are better understood by elementary and preschool students when taught through traditional games like engklek. Furthermore, 8 articles presented experimental studies showing that innovative designs integrating engklek into geometry instruction significantly improve problem-solving skills, numerical literacy, and geometric literacy. Effective instructional models for geometry learning include Realistic Mathematics Education (RME), RME with the Hypothetical Learning Trajectory (HLT) approach, PMRI, didactic designs, and the development of student worksheets (LKPD). This review concludes that integrating geometry learning with engklek ethnomathematics offers an engaging and culturally relevant approach to overcoming students’ fear of mathematics while improving their mathematical literacy and reasoning skills